Iron deficiency anemia and levels of oxidative stress induced by treatment modality - Akarsu, Saadet; Demir, Hatice; Selek, Sahabettin; Oguzoncul, Ferdane (Wiley-Blackwell, 2013)
Background The effects of iron deficiency anemia (IDA) and its treatment on plasma total antioxidant capacity (TAOC) were investigated. Methods Sixty patients with IDA and 20 healthy controls were divided into four subgroups: an oral (per os: PO) group (n = 20); an intramuscular (IM) group (n = 20); an intravenous (IV) group (n = 20); and the control group (n = 20). Blood samples were obtained from all patients before treatment, and at 24h, 7 days, 6 and 13 weeks after initiation of IDA therapy. Results TAOC in the IDA group was low when compared with the control group (P < 0.001). Although TAOC at 24h in the PO group was not different from the control group, the TAOC in the IM and IV groups was relatively lower (P < 0.001). The TAOC in the PO group at 7 days, and at 6 and 13 weeks was closest to the control group level. The mean TAOC in the IV group at 13 weeks was clearly lower relative to the PO and IM groups. Conclusions Oxidative stress was minimally induced with oral therapy, while IM and IV therapies induced higher levels of oxidative stress, in increasing order of intensity.
Keywords: intramuscular; intravenous; iron deficiency anemia; oral; total antioxidant capacity; treatment